Teaching "Narratives of Slavery" in Charleston, SC – Slavery Central. Issue 3 (2nd July 2016) - Lewis, Simon
Abstract: This essay describes a graduate course entitled "Narratives of Slavery" taught in Charleston, SC in spring 2014, in which I sought to recenter the dominant (national) discourse on slavery by stressing the local and insisting on our (the class's) implication with the structures of things past, both the physical structures of the city of Charleston, and all of the legal, financial, historiographical, and ideological structures of the Atlantic World that continue to shape our contemporary reality. The course attempted to critically analyze the process and the consequence of narrativizing slavery – how we write slavery into (and out of) being; how we use narratives of slavery for the purpose of abolition and emancipation; what happens when we write particular narratives of slavery; what gets written out of the history of slavery when particular narratives become dominant; how contemporary narratives of slavery feed into and compare with historical accounts; how historical accounts feed into historical fiction, and how all these things play out in the postcolonial here and now of the American South in the age of Obama (and anti-Obama). In addition to offering a set of critical readings of texts, notably Zakes Mda's neo-slave narrative Cion, the essay also presents some of the students' thoughtful and moving responses to the texts and to Charleston's evolving memorial landscape. The essay's claim that we must read and discuss slavery and race in ways that do not reify or ossify either of those two terms was given even more urgency by the horrific mass shooting of 17 June 2015.